OC-88 Clinical and genetic characteristics, diagnosis, treatment and outcome in patients with mucopolysaccharidosis tipe i and tipe ii in our country. (6th June 2017) - Alkhzouz, Camelia; Bucerzan, Simona; Nascu, Ioana; Lazea, Cecilia; Asavoaie, Carmen; Grigorescu-Sido, Paula
Abstract : Introduction: Mucopolysaccharides (MPS) are a group of rare diseases with chronic progression caused by excessive intralysosomal accumulation of glycosaminoglycans (GAG), due to certain acid hydrolases deficiencies. The unchanged mucopolysaccharides accumulate in the lysosomes of reticuloendothelial system cells, resulting in severe functional and structural alterations in various tissues and organs. Aim of the study was to assess the clinical, genetic characteristics and outcome under enzyme replacement treatment (ERT) of Romanian MPS type I and type II patients. patients and methods: The study group included five MPS type I and nineteen MPS type II patients (4 girls and 20 boys), aged between 1–14 years. The study methods consisted in: clinical and standard auxological assessment; goniometry; neurological and psychological evaluation; otorhinolaryngology examination with audiogram, ophthalmological examination, cardiology evaluation (ECG, Doppler echocardiography), spirometry, ultrasonography, specific enzyme activity assay and molecular analysis (PCR and sequencing). Results: All patients presented coarse facial features, organomegaly, arthropathy, cardiac involve-ment and respiratory difficulties, but variable neurological impairment. The clinical onset was at 1.53±0.74 years; the unspecific diagnosis was established at 4.86±8.6 years and specific diagnosis at 5.84±6.2 years. Molecular analysis revealed 11 unreported mutations. ERT was started at 7.7±5.28 years (limits between 1.5 years and 20.25 years). ERT reduces organomegaly and ameliorates rate of growth, joint mobility, reduces the number of episodes of respiratory infections, but does not prevent deterioration of cognition and other neurologic functions. Conclusions: An important gap between the clinical onset and specific diagnosis resulted in this group. The ERT should be started at an early age prior to irreversible injuries installation.